Penegakan Pengawasan Mahkamah Kehormatan Mahkamah Konstitusi Terhadap Hakim Konstitusi - Niken, Niken; Khalid, Khalid (Faculty of Law, Andalas University, 2023)
This research aims to determine the important role of the Constitutional Court Ethics Council in upholding the integrity and ethics of constitutional judges and in upholding law and justice in Indonesia.